Factors associated with successful passing test for medical certificate in 5 specialties - Mussagazin, Anuar (Nazarbayev University School of Medicine, 2019)
The efficiency of the health-care system and the quality of medical services are directly related to the performance of medical professionals. Examination for obtaining a medical license allows the protection of the public by ensuring high-quality medical care from skilled specialists. This research will analyze the stratified data in passing rate (more than 50%) by demographic factors (region, nationality, age, gender) and 5 the most common specialties (general surgery, therapeutics, pediatrics, obstetrics, general practice). The identification of the risk groups will help them to prepare and successfully pass the exam for medical certification.
Keywords: health-care system